(untitled) (European Journal of Pure and Applied Mathematics, 2011)
In this paper, by using b*-set [24] we introduce a new class of sets called b*g-closed sets, which is stronger than g-closed sets and weaker than closed sets. We define two new separation axioms called b*T1/2 and b**T1/2 spaces as applications of b*g-closed sets. The notions b*g-continuity and b*g-irresoluteness are also introduced.